Pengaruh Penyuluhan Pertanian terhadap Efisiensi Teknis Usahatani Padi di Desa Tanjung Kabupaten Pamekasan - Rabbani, Bintang Cahya; Priyanto, Moh. Wahyudi; Kurniyanto, Ifan Rizky (Journal of Integrated Agribusiness, 2025)
A national decline in rice production of 0.036 million tons per year during the 2019–2023 period, accompanied by an increase in rice consumption of 0.753 kilograms per capita per year, has resulted in an imbalance between supply and demand, thereby prompting Indonesia to import rice. One of the strategies implemented by the government to boost agricultural productivity is through agricultural extension services. This study aims to analyze the effect of agricultural extension on the technical efficiency of rice farming in Tanjung Village, Pamekasan Regency. The analytical approach employed is Stochastic Frontier Analysis (SFA) using a Cobb-Douglas production function model. The total population of farmers in the research area comprised 130 individuals, from which 100 respondents were selected using a simple random sampling technique. The findings indicate that the average technical efficiency of farmers is only 53.6%. Land area, seed, and urea fertilizer were found to have a significant effect on production, while age, education, land ownership status, and participation in extension activities influenced inefficiency levels. Farmers who participated in extension programs were found to be more efficient than those who did not. These results highlight the importance of sustaining and improving the quality of agricultural extension services to support national food security. The government is expected to increase the number of officers overseeing agricultural activities in rural areas to enhance productivity.